A Cross-Sectional Study To Analyse The Prevalence Of Dysmenorrhea With Its Associated Complaints And Management Strategies Among Students Of Rawalpindi Medical University - Javeria Sehir, Javeria Sehir; Ghalia Fatima, Ghalia Fatima; Sidra Hamid, Sidra Hamid; Maryam Sohail, Maryam Sohail; Eeshal Fatima, Eeshal Fatima (Resident Journal of Rawalpindi Medical University, 2024)
Objective: To study prevalence of dysmenorrhea, its impact on daily routine, the associated complaints and the symptomatic management by the medical students at RMU. Methods: Our research was based on a cross-sectional study from Aug 2023 to Dec 2023. Questionnaires were distributed among medical students of RMU with total participants of 170. Collected data was analyzed using SPSS version 27.0. The chisquare test was used for evaluation. Simple frequencies, percentages, and mean were obtained. Results: We collected responses from 170 participants. Mean age of respondents was 20.59 ± 1.5 years. Based on the data we collected, we found that 70% of the respondents experienced dysmenorrhea with varying frequency. Dysmenorrhea had a considerable impact on students’ daily life activities. 45% of the participants faced productivity issues, 28% experience emotional stress while 23.5% reported they avoid social events and 19% even miss school. Several complaints were associated with dysmenorrhea experience; most common were muscle cramps (45%), back pain (40.5%), nausea (27%) and fatigue (27%). We also investigated that majority of the students use self-management strategies to overcome their symptoms, which mainly included relying on pain relievers (36%) and use of heat therapy (37%). Use of herbal remedies was also common among 34% participants. 28% of the respondents had daily exercise routine, 19% avoid junk and 36% avoid cold water during menstruating days. Conclusion: The study revealed that primary dysmenorrhea is a prevalent complaint among female at RMU, which severely affects their daily life. Meanwhile the myalgia, digestive, mental, physical, sleep, and appetite issues were self-managed by 63% while 37% sought medical help. The most prevalent symptomatic management are over the counter medicines, heat therapy some practice herbal remedies as well. Keywords: dysmenorrhea, medical student, associated symptoms, pain relievers